Contextualism In Architecture: The Design of Office Building in Heritage Context - Pandhu Putra Pratama; Arina Hayati; Asri Dinapradipta (Journal of Architecture & Environment, 2022)
The discussion starts with a question regarding why most of office buildings use the international style as their building expression. The first initial investigation is carried out by studying several precedents adapted from the rationalist and modern movement era. International style has architectural characteristics such as a simple form, pure structure, simple geometry, glass wall facade, and form follows function. This style mostly shows a lack of identity that does not respond to the local value and expression. The architectural buildings become placeless and do not represent the place with specific environmental responses and identity (contextual architecture). Additionally, an office building should be able to respond to the users’ activities and their identity/characters. This paper is based on the process of design project from design thinking, design research, and design process to conceptual design proposal. Design thinking is started by asking the question “what if” the new building design proposal reverses the international style’s facts through literature studies. The goals are to create the latest concepts that express their own character and image to portray both the users' characters and the location, which is human and environmentally friendly, using contextual analysis. Next, the design process includes explaining and arguing the process from proposing the design concept to building transformation. Some methods are used to determine the ‘big idea’ and design criteria and parameters, including the first principle, domain-to-domain transfer, and responding to site. The design proposal expresses the building heritage and its atmosphere, users’ characteristics, and has low energy efficiency. The design results highlight the aspect of "value of site" and “character of the building user” are essential to create the building image and identity.